Electron power absorption in radio frequency driven capacitively coupled chlorine discharge. (4th June 2021) - Proto, A; Gudmundsson, J T
Abstract: Particle-in-cell Monte Carlo collision simulations and Boltzmann term analysis are applied to study the origination and properties of the electric field and the electron power absorption within the electronegative core of a capacitively coupled discharge in chlorine as the pressure is varied from 1 to 50 Pa. The capacitively coupled chlorine discharge exhibits high electronegativity and high electric field develops within the electronegative core. It is found that the electron power absorption increases and the ion power absorption decreases as the pressure is increased. At 1 Pa the electron power absorption is due to both the pressure and ohmic terms. At the higher pressures >10 Pa the ohmic term dominates and all the other contributions to the electron power absorption become negligible. Therefore, the discharge becomes increasingly ohmic with increased pressure and eventually behaves as a resistive load.